Spatial-temporal evolution of sediment transport in the upper Yangtze River Basin considering the cumulative impacts of mega reservoirs - Wang, Keyuan; Huang, Lei; He, Guojian; Fang, Hongwei; Chen, Minghong; Wang, Dianchang; Wu, Xinghua (Catena (Giessen), 2023)
•A mathematical model considering the operation of 24 mega reservoirs was proposed.•The sedimentation mainly occurs in the mainstream during the flood season.•The cascade reservoirs operation leads to easier and prolonged sedimentation. The intensive construction of large dams in the upper Yangtze River Basin (UYRB) has formed large-scale cascade reservoirs and obviously altered the flow regime and sediment transport of the basin. However, few studies have quantitatively described the cumulative impact of these reservoirs on sediment interception. In this study, a flow and sediment transport model that fully considers the operation processes of 24 mega reservoirs in the UYRB was established, and the spatial and temporal variations in sedimentation from 2011 to 2080 were elucidated, assuming repeated series of daily input flow discharge and sediment concentration during 2011–2020 and monthly water operation levels of 24 reservoirs during 2018–2021 as boundary conditions. The results showed an annual average sedimentation of more than 300 Mt in the UYRB during 2011–2060, which falls to 270 Mt in the period 2061–2080, and more than 80% of the sedimentation occurs in the flood season. Nearly 80% of the total sedimentation during 2010–2080 was observed in the mainstream reservoirs, especially the four mega reservoirs in the lower Jinsha River and the Three Gorges Reservoir (TGR), which accounted for 31.9% and 22.7% of the total sedimentation, respectively. The proportion of sedimentation in mainstream reservoirs will further increase with increasing operation periods. Most reservoirs in the UYRB will not reach sedimentation equilibrium by 2080, except for reservoirs in the Min River Basin. The ratio of siltation capacity to average annual sediment yield determines the percentage of residual siltation capacity of each reservoir. The operation of the cascade reservoirs in 2013–2020 had no more immediate impact on the middle and lower Yangtze River than that in 2003–2012, when the TGR started impoundment. However, the joint operation of these cascade reservoirs has changed the spatial distribution of sedimentation in the UYRB, and will lead to prolonged impacts on downstream channel erosion.